Blue‐light receptor phototropin 1 suppresses immunity to promote Phytophthora infestans infection. Issue 5 (8th January 2022) - Naqvi, Shaista; He, Qin; Trusch, Franziska; Qiu, Huishan; Pham, Jasmine; Sun, Qingguo; Christie, John M.; Gilroy, Eleanor M.; Birch, Paul R. J.
Summary: Blue‐light (BL) phototropin receptors (phot1 and phot2) regulate plant growth by activating NPH3/RPT2‐like (NRL) family members. Little is known about roles for BL and phots in regulating plant immunity. We showed previously that Phytophthora infestans RXLR effector Pi02860 targets potato (St)NRL1, promoting its ability to enhance susceptibility by facilitating proteasome‐mediated degradation of the immune regulator StSWAP70. This raises the question: do BL and phots negatively regulate immunity? We employed coimmunoprecipitation, virus‐induced gene silencing, transient overexpression and targeted mutation to investigate contributions of phots to regulating immunity. Whereas transient overexpression of Stphot1 and Stphot2 enhances P . infestans colonization of Nicotiana benthamiana, silencing endogenous Nbphot1 or Nbphot2 reduces infection. Stphot1, but not Stphot2, suppressed the INF1‐triggered cell death (ICD) immune response in a BL‐ and NRL1‐dependent manner. Stphot1, when coexpressed with StNRL1, promotes degradation of StSWAP70, whereas Stphot2 does not. Kinase‐dead Stphot1 fails to suppress ICD, enhance P. infestans colonization or promote StSWAP70 degradation. Critically, BL enhances P. infestans infection, which probably involves phots but not other BL receptors such as cryptochromes and F‐box proteins ZTL1 and FKF1. We demonstrate that Stphot1 and Stphot2 play different roles in promoting susceptibility, and Stphot1 kinase activity is required for BL‐ and StNRL1‐mediated immune suppression.